Effectiveness of a school‐based academic asthma health education and counseling program on fostering acceptance of asthma in older school‐age students with asthma. Issue 1 (30th November 2014) - Kintner, Eileen K.; Cook, Gwendolyn; Marti, C. Nathan; Gomes, Melissa; Meeder, Linda; Van Egeren, Laurie A.
Abstract Purpose The purpose of this study was to evaluate the effectiveness of the academic asthma education and counseling Staying Healthy–Asthma Responsible and Prepared™ (SHARP) program on fostering psychosocial acceptance of asthma. Design and Methods This was a phase III, two‐group, cluster‐randomized, single‐blinded, longitudinal study. Students from grades 4 and 5 (N = 205) with asthma and their caregivers completed surveys at pre‐intervention and at 1‐, 12‐, and 24‐months post‐intervention. Analysis involved multilevel modeling. Results All students demonstrated significant improvement in aspects of acceptance; students in SHARP demonstrated significant improvement in openness to sharing and connectedness with teachers over students in the control condition. Practice Implications The SHARP program offers a well‐tested, effective program for psychosocial acceptance of asthma, which is welcomed by schools.